A new primary standard oil manometer for absolute pressure up to 10 kPa. (9th January 2015) - Li, Yanhua; Yang, Yuanchao; Wang, Jinku; Sun, Junfeng
Abstract: The National Institute of Metrology has developed a new oil manometer that covers the absolute pressure range from 100 Pa up to 10 kPa. The manometer is based on the ultrasonic measurement of transit time in oil columns, and a novel dual U-tube system has been designed to measure the speed of sound in real time as the pressure changes. The working fluid, di-2-ethylhexyl sebacate, was chosen for its sufficiently low vapor pressure and low sound attenuation. Each tube has a coating of Teflon to resist wetting by the oil. To obtain a uniform and stable temperature environment, the dual U-tube system is located inside a guard vacuum chamber that is wrapped with foam and aluminium foil. A vertical temperature difference of less than 20 mK, a horizontal temperature difference of less than 5 mK and a temperature stability better than 10 mK were achieved. The overall standard ( k = 1) uncertainty of the oil manometer is estimated to be approximately (0.015 + 1.63  ×  10 −5   p  Pa −1 ) Pa for absolute pressure measurements.